Pyruvate kinase type M2 promotes tumour cell exosome release via phosphorylating synaptosome-associated protein 23 - Yao Wei (Nature Portfolio, 2017)
Exosomes, vesicles secreted by cancer cells, have a role in cancer progression but the mechanisms regulating their biogenesis are mostly unknown. Here the authors show that PKM2, a rate-limiting glycolytic enzyme overexpressed in cancer cells, mediates exosomes exocytosis by phosphorylating SNAP-23.